New Method for Nanosecond Laser Machining - Toro Salazar, Cinthya Emma (2012)
The technique of micro-machining assisted by laser is the most recent and flexible process for the design of complex devices. To be able to micro-machine hard materials with precision it is necessary to study the parameters that control and limit the capabilities of this laser process. Several articles have shown that if it applies a lot of energy in a localized area there are hot-affected zones (HAZ), even when a femtosecond laser is used. Hence, the challenge in the laserbased micromachining is to improve the quality of machining, i.e. depleting the HAZ in the prototypes. In this work, changing the optical properties of the substrate, good quality silicon micro-machining has been obtained with a nanosecond Q-switched laser.